The Pentahelix Role in Tourism Destination Management Sebangau National Park Palangka Raya City - Wilantari, Ni Nyoman Ayu; Lanya, Indayati; Suardana, I Wayan; Adikampana, I Made (International Journal of Multidisciplinary Sciences, 2024)
The existence of Sebangau National Park in Central Kalimantan is a government effort to save and protect ecosystems that have started to deteriorate in the Sebagau area due to logging, poaching, and forest burning for land clearing conducted illegally by the community. In addition to these problems, the existence of Sebangau National Park is also to minimize the impact caused by global warming in the form of high air temperatures, which can trigger forest and peatland fires which occur almost every year in Palangka Raya City. Forest fires can damage ecosystems, releasing carbon and greenhouse gases into the atmosphere so that they can pollute water, soil and air. In addition, the smoke produced can also interfere with public health. The involvement of Pentahelix actors in the management of the Sebangau National Park tourism destination in Palangka Raya City is to make tourism at this destination sustainable. This research is designed as qualitative research supported by quantitative data, often referred to as a mixed method. Data collection was conducted through observation, semi-structured interviews, document studies, and questionnaires. The analysis method used in this study is Interpretative Structural Modeling (ISM) to map the role of Pentahelix with three elements consisting of: actor elements, need elements, and constraint elements. The ISM analysis results identified the main actors in the management of the Sebangau National Park tourism destination in Palangka Raya City as the Sebangau National Park Office in Palangka Raya City (government) and the Getek Maju Mandiri Group (community). The primary need in management is the Pentahelix collaboration and sustainable ecotourism. The main constraints in management are the incomplete availability of facilities and infrastructure and the lack of coordination between the government, private sector, and community.